2011
DOI: 10.1308/003588411x579801
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cell salvage versus postoperative autologous blood transfusion in hip arthroplasty: a retrospective service evaluation

Abstract: INTRODUCTION A number of ways of reducing blood loss in arthroplasty have been explored, including preoperative autologous transfusion, intraoperative cell salvage and postoperative autologous transfusions. Both intraoperative blood salvage and postoperative retransfusion drains have been shown to be effective in reducing blood loss in total hip arthroplasty. In our department there was a change in practice from using postoperative retransfusion drains to intraoperative cell salvage. To our knowledge no study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Similar results were found by Lisander et al [12]. However, a current study by Mason et al reported that intraoperative cell salvage is the preferred method to avoid major blood loss compared to postoperative transfusion [13]. Focusing on the results in patients undergoing TKA, blood loss was neither influenced by the patient's BMI nor by the ASA score in the current cohort.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were found by Lisander et al [12]. However, a current study by Mason et al reported that intraoperative cell salvage is the preferred method to avoid major blood loss compared to postoperative transfusion [13]. Focusing on the results in patients undergoing TKA, blood loss was neither influenced by the patient's BMI nor by the ASA score in the current cohort.…”
Section: Discussionsupporting
confidence: 84%
“…Especially for patients with rare blood types, patients who have been transfused with allogeneic blood and produced irregular antibodies, and patients with other blood matching problems, this technology is of great significance (53), and provides convenience for elective surgeries. The most prominent clinical features of ABT is that it can instantly provide patients with fresh blood that has identical type, quickly replenish the patient's blood volume, and improve oxygen carrying capacity (54,55), maintaining an effective blood circulation. In addition, autologous blood has low acid content and normal K + concentration, relatively higher 2,3-diphosphoglycerate levels and provides better cell vitality, preventing complications such as hyperkalemia.…”
Section: Development Trends and Challenges Of Abtmentioning
confidence: 99%
“…Autologous blood collection techniques, such as ICS, have been the source of debate over the last 30 years since their introduction. While the benefits of blood salvage in Orthopaedic surgery have been well described [9,21,28–32] , there remain concern that it should be used more discriminatingly. These concerns may stem from a number of studies that have shown ICS to either be ineffective or costly, across a number of other surgical specialities [2,25,33] .…”
Section: Discussionmentioning
confidence: 99%
“…As half of all units transfused in the UK are used for surgical patients [8] , a blood conservation technique like ICS seems well placed to help reduce the national use of allogenic blood. Although ICS can also be successfully carried out in knee arthroplasty, it has been shown to be less effective than ICS in hip arthroplasty [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation